TOPENG JOKO BLUWO DALAM PERTUNJUKAN WAYANG TOPENG JENGGLONG JOYO, MOJOSONGO, SURAKARTA - Kristian Mulyaningtyas (Greget, 2015)
The object of this research is the masked dance Joko Bluwo, or topengJoko Bluwo, which isfound in Padepokan Jengglong Joyo, Mojosongo, Surakarta, and is a form of folk dance that hasgrown and developed in Surakarta, in particular in the Mojosongo area. The research aims tolearn more about the existence of the arts that are found in Padepokan Jengglong Joyo, Mojosongo,Surakarta, focusing specifically on the movements in the choreography of topeng Joko Bluwo andthe movements of the character of Joko Bluwo. A qualitative method is used to explain the information that was obtained in the field through an ethnochoreological approach. The data wascollected using an interactive method and then analyzed descriptively. The results of the researchshow that topeng Joko Bluwo has a unique character which can be recognized from the shape of themask, the voice, and the movements, in which the arms stretch no higher than the shoulders andthe legs are opened no wider than the width of the body.Keywords: Topeng Joko Bluwo, Padepokan Jengglong Joyo, Choreography, Unique Movements.